1985
DOI: 10.1677/joe.0.1050189
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intravenous bovine growth hormone or human pancreatic growth hormone-releasing factor on milk production and plasma hormones and metabolites in sheep

Abstract: Although it is well known that exogenous bovine GH (bGH) increases milk yield in ruminants it has not been possible to determine whether an increase in endogenous GH secretion has the same effect. The recent isolation of human pancreatic GH-releasing factor (hpGRF-44) has enabled this comparison of the effects of bGH and hpGRF-44 on milk production in sheep. Three pairs of Dorset ewes underwent three 4-day treatments according to a Latin square design. Treatment 1 involved: 2-hourly i.v. injections (approximat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
18
0

Year Published

1987
1987
2000
2000

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 24 publications
6
18
0
Order By: Relevance
“…In this respect the present results are consistent with results of previous short-term studies with sheep (Dracy and Jordan 1954;Jordan and Shaffhausen 1954;Hart et al 1985;McDowell et al 1988), goats (Hart et al 1983;Mepham et al 1984) and dairy cattle (see McCut~heon and Bauman 1985;McDowell 1985;Johnsson and Hart 1986). Similarly, the present results with sheep are in conformity with results of previous longterm studies with dairy cows Peel et al 1985;Chalupa et al 1987).…”
Section: Discussionsupporting
confidence: 92%
“…In this respect the present results are consistent with results of previous short-term studies with sheep (Dracy and Jordan 1954;Jordan and Shaffhausen 1954;Hart et al 1985;McDowell et al 1988), goats (Hart et al 1983;Mepham et al 1984) and dairy cattle (see McCut~heon and Bauman 1985;McDowell 1985;Johnsson and Hart 1986). Similarly, the present results with sheep are in conformity with results of previous longterm studies with dairy cows Peel et al 1985;Chalupa et al 1987).…”
Section: Discussionsupporting
confidence: 92%
“…The present results are consistent with results of a limited number of previous studies which have shown that exogenous GH is galactopoietic in the lactating ewe (Dracy and Jordan 1954;Jordan and Shaffhausen 1954;Hart et al 1985;McDowell et al 1987c). Thus, milk yield and the yields of the major milk constituents were increased and milk fat content was raised during injections of GH.…”
Section: Tissue Blood Flowssupporting
confidence: 93%
“…Although it is well documented that growth hormone (GH) increases milk production in cows Bines et al 1980;Peel et al 1981Peel et al , 1982, sheep (Dracy and Jordan 1954;Jordan and Shaffhausen 1954;Hart et al 1985) and goats Mepham et al 1984), the mechanisms by which the hormone exerts galactopoietic effects remain unclear. Bines et al (1980) and also raised the possibilities that GH acts directly or indirectly on the mammary gland or, alternatively, influences the supplies of key nutrients to the mammary gland, thereby influencing the capacity of the mammary gland to synthesize milk.…”
Section: Introductionmentioning
confidence: 99%